The investigation of load carrying capacity of elastic-plastic strain hardening bisteel i-section beams - Jaras, Arūnas; Kačianauskas, Rimantas (Journal of Civil Engineering and Management, 2002)
In the present study, CPT is modelled by static elastic-plastic small strain finite element method (FEM) analysis of axi-symmetric problem. Undrained soil properties and Tresca yield criterion is used for determining cone resistance of clay. Sand is modelled by using drained soil properties and Mohr-Coulomb yield criterion. Cone penetration problem is formulated as a collapse load problem. Associated and non-associated flow rules were used for modelling. A number of numerical experiments were performed to determine rational size of discrete region. Received dimensions of region were used for further research. Cone factor Nc for clay was obtained and the comparison of Nc values with other theoretical solutions is presented. A conclusion may be made that the limit of the validity of geometrically linear systems has been reached. The evaluation of the effect of cone penetration requires the analysis of large strains to be made.Article in Lithuanian.First Published Online: 30 Jul 2012